Recommendations for Teaching English for Vocational High Schools Using an English for Specific Purposes (ESP) Approach and Whole-Part-Whole (WPW) Design - Sujana, I Made; Melani, Boniesta Zulandha; Saputra, Agus; Apgrianto, Kurniawan; Munandar, La Ode Alfin Haris (Program Studi Pendidikan Bahasa Inggris, 2024)
Learning English for VHS students should be directed at mastering the ability to use English for communication in their respective fields. However, field observations show that the ability to use English remains a challenge for most VHS students due to various obstacles. This study aims to develop an innovative teaching module model to support the implementation of teaching English for Vocational Schools (TEVHS). This is qualitative reserach using survey method. It was conducted at VHS in Mataram Lombok, involving 23 English teachers from VHS English Teachers’ Forum (MGMP VHS). The data were collected using triangulation techniques such as a questionnaire, focus group discussion (FGD), ducummentary. The collected data were then analyzed qualitatively using Miles & Hubbermen’s Model consisting of data reduction, data presentation, and conclusion. Based on the analysis, the conclusions are as follows: (1) English learning for VHS students needs to be reconstructed to meet the demands of the workforce. With the diverse requirements of various occupations, the design of TEVHS must be based on the English for Specific Purposes (ESP) approach; (2) TEVHS must be designed to instill communication skills by providing various inputs from receptive skills (Listening, Reading, and Viewing) which can be used as models for language production (Speaking, Reading, Presenting). To enhance innovation in learning, it is recommended that the design of TEVHS integrate such approach and model as ESP, Whole-Part-Whole, and TPACK to overcome various problems.